Integrative analysis of single-cell and transcriptome sequencing with experimental validation reveals PKHD1L1 as a novel biomarker in lung adenocarcinoma - Xiangqian Zhang; Jie Wang; Hanyang Su; Xiaojin Liu (Scientific Reports)
Abstract Polycystic kidney and hepatic disease 1-like protein 1 (PKHD1L1) is predicted to encode a large type I transmembrane protein involved in hearing transmission and mediating cellular immunity under physiological conditions. However, its role in cancer progression, especially in lung adenocarcinoma (LUAD), has not been fully elucidated. In this study, we observed significantly lower expression of PKHD1L1 in LUAD tissues than in normal lung tissues on the basis of the integration of public datasets from the TCGA and GEO cohorts. Furthermore, we found that low PKHD1L1 expression was a strong predictor of poor prognosis in patients with LUAD. Pathway enrichment analyses revealed that PKHD1L1 is associated primarily with asthma and multiple immune processes. Through meticulous analysis of immune cell infiltrates and single-cell datasets, we discerned a notable correlation between the expression of PKHD1L1 and the presence of B cells, with a particularly strong association observed in plasma cells. This finding led us to believe that the role of PKHD1L1 may extend beyond its previously reported involvement in cellular immunity, potentially impacting humoral immunity as well. In vitro experiments revealed that the over-expression of PKHD1L1 significantly inhibited the proliferation and migration ability of LUAD cell lines. These findings suggest that PKHD1L1 is an important prognostic indicator and a potential therapeutic target for LUAD.